If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 + 3x = 34.60 Solving 25 + 3x = 34.60 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + 3x = 34.60 + -25 Combine like terms: 25 + -25 = 0 0 + 3x = 34.60 + -25 3x = 34.60 + -25 Combine like terms: 34.60 + -25 = 9.6 3x = 9.6 Divide each side by '3'. x = 3.2 Simplifying x = 3.2
| -6y+1=-7y+7 | | 3(2x+2)=9x+4-3x+2 | | 2x^3+X^6-15=0 | | X^4=x^2 | | 3(y-10)+1=x(y-8) | | 5-x-2=3+x+5 | | 9x+8x-65=139 | | 11(k-1)=7(k-y) | | x+2y=3w | | 14-(x+m)=3(x+9)-10 | | 14x+12.5=14x | | 6x-24-2x+2=6x-9 | | 5-2(8n+8)=11 | | -x-5x-47=37 | | 9m-3(m+6)=2(m+1) | | 9(x+4)=8(x+5)+x | | 4x+3y-4=-16 | | x+0.02x=288 | | y(2)=2x+1 | | -2(4w-8)+7w=7(w+4) | | -43-4x+x=17 | | 2x^2=108 | | 8(t-2)+4t=4(3t+4)-12 | | x^2+12x-216=0 | | 4x+3y-4=16 | | 4(u-3)-8=-2(-7u+6)-4u | | 3(2x-8)=-4(3x+2) | | 8p-2=6p+6 | | -t+2t+15=0 | | -1(3z+4)=6z-3(3z+2) | | -4(9x-1)=-14 | | -2v-44=4(v+4) |